Do faster swimmers spend longer underwater than slower swimmers at World Championships? - Veiga, S.; Roig, A.; Gomez-Ruano, M. A. (European Journal of Sport Science, 2016)
The main objectives of the present research were (1) to examine the relationships between the distances travelled underwater during the start and turn segments with swimming race performance at the elite level and (2) to determine if the individualised-distance start and turn parameters affect the overall race performance. The race parameters of the 100 and 200 m events during 2013 World Championships were measured by an innovative image-processing system (InThePool® 2.0). Overall, 100 m race times were largely related to faster start velocities in men's breaststroke and freestyle events. Conversely, overall, 200 m race times were largely related to longer starting distances in the women's butterfly events, to longer turn distances in men's and women's backstroke and women's butterfly events and to shorter turn distances in women's freestyle events. Changes on the start or turn velocities could represent moderate time improvements in most of the 100 m events, whereas modifications on the start or turn distances (especially in the last turn) could provide elite swimmers with time improvements of practical importance on the 200 m events. The evaluation of races by individualised-distance parameters should be provided to elite swimmers in order to decide the most appropriate race segment configuration for each event.